2005
DOI: 10.1111/j.0011-1348.2005.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

The Missing Link in General Deterrence Research*

Abstract: Research on the deterrent effects of punishment falls into two categories: macro-level studies of the impact of aggregate punishment levels on crime rates, and individual-level studies of the impact of perceived punishment levels on self-reported criminal behavior. For policy purposes, however, the missing link-ignored in previous research-is that between aggregate punishment levels and individual perceptions of punishment. This paper addresses whether higher actual punishment levels increase the perceived cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(163 citation statements)
references
References 20 publications
4
150
1
1
Order By: Relevance
“…Their study concluded that variation in sanction certainty and severity predicted offending, whereas variation in celerity did not. A telephone survey of adults' perceptions of punishment certainty, severity, and swiftness of punishment did not find that celerity of actual punishment had an effect on respondents' perceptions of punishment (Kleck et al, 2005; see also Piquero et al, 2012). A similar study by Kleck and Barnes (2008) aggregated these perceptions up to the county level and found that average local population perceptions of the certainty, severity, and swiftness of punishment were not related to actual levels of punishment at the county level.…”
Section: Assessing the Effects Of Celeritymentioning
confidence: 97%
See 1 more Smart Citation
“…Their study concluded that variation in sanction certainty and severity predicted offending, whereas variation in celerity did not. A telephone survey of adults' perceptions of punishment certainty, severity, and swiftness of punishment did not find that celerity of actual punishment had an effect on respondents' perceptions of punishment (Kleck et al, 2005; see also Piquero et al, 2012). A similar study by Kleck and Barnes (2008) aggregated these perceptions up to the county level and found that average local population perceptions of the certainty, severity, and swiftness of punishment were not related to actual levels of punishment at the county level.…”
Section: Assessing the Effects Of Celeritymentioning
confidence: 97%
“…While there is ample empirical evidence assessing the deterrent effects of certainty and much less so with respect to severity (see Nagin, 2013;Piquero, Paternoster, Pogarsky, & Loughran, 2011), less is known about the effects of celerity, or the time elapsed between the commission of an offense and its punishment. While a handful of studies have considered the potential deterrent effects of celerity (see Howe & Loftus, 1996;Kleck, Sever, Li, & Gertz, 2005;Nagin & Pogarsky, 2001;O'Connell, Visher, Martin, Parker, & Brent, 2011;Pestello, 1984) there is little consensus as to whether swift punishment provides for a deterrent effect. Further, celerity has historically been defined by the time between arrest and criminal sentence, leaving other 'punishments' such as pre-sentence punishments (e.g., arrest and jailing), relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Important recent work includes that of Kleck et al (2005) and Kleck and Barnes (2013), who conducted a telephone survey of 1,500 adults in fifty-four large urban counties in the United States. They asked each individual to estimate case clearance rates, the probability of serving time in prison, and maximum sentence for several different serious felonies.…”
Section: Perceptions and Deterrencementioning
confidence: 99%
“…Few studies have investigated the relationship between law enforcement indicators and variations in the public perceptions about the properties of punishment (Kleck et al, 2005;Homel, 1988). In his seminal work on random breath testing (RBT) in New South Wales, Australia, Homel (1988) shows that the introduction of RBT was used as an argument to resist peer pressure to drink-and-drive.…”
Section: Directions For Future Studiesmentioning
confidence: 99%